Effects of an in-season plyometric training program on repeated change of direction and sprint performance in the junior soccer player - Hammami, M.; Negra, Y.; Aouadi, R.; Shephard, R. J.; Chelly, M. S. (The Journal of Strength and Conditioning Research, 2016)
We aimed to determine the gains in explosive movements of male junior soccer players induced by incorporating an 8-week plyometric training program (PTP) into a standard soccer conditioning regimen 5 months after the beginning of the competitive season. Our hypothesis was that PTP would enhance explosive movements, and thus sprint running, repeated shuttle sprint ability (RSSA), agility and the ability to make repeated changes of direction (RCOD). A group of junior soccer players were randomly divided into 2 groups: an experimental group (E, n = 15, age 15.7 ± 0.2 years) and a control group (C, n = 13, age 15.8 ± 0.2 years). The participants in E and C performed training exercises and matches together, but for an 8-week period in the latter part of the season, the experimental group replaced a part of the normal regimen (the tactical session) by a biweekly course of PTP (hurdle and drop jumps). Two familiarization sessions were held 2 weeks before definitive testing. The ability of the players was assessed by 3 agility tests (a sprint test with 180° turns, a 9-3-6-3-9 m sprint with backward and forward running, and a four 5-m sprint test with turns); 2 repeated sprint tests (RSSA and RCOD); and running times over 5-, 10-, 20-, 30-, and 40-m distances. Participants in E showed gains relative to C in sprint times (p = 0.05 for 5, 10, and 20 m), and 2 of 3 the RCOD parameters (RCOD best, p = 0.001; RCOD total, p = 0.05). However, with the pattern of plyometric training that we adopted, and perhaps because participants were in good initial physical condition, the agility and RSSA test scores remained unchanged. Nevertheless, we conclude that our PTP can be commended to junior soccer players as a means of improving important components of their physical performance.